2014
DOI: 10.5902/2179769210519
|View full text |Cite
|
Sign up to set email alerts
|

Significado da amamentação vivenciado por mães nutrizes

Abstract: RESUMO: Buscou-se compreender os significados e concepções sobre amamentação vivenciadas por nutrizes. Estudo descritivo, analítico com abordagem qualitativa, aprovado pelo Comitê de Ética em Pesquisa. Os dados foram coletados com 24 nutrizes, residentes no interior da Paraíba, que participaram de um grupo de extensão, no ano de 2007, por meio de entrevista, gravada, estimulada por imagens. Os dados foram analisados após transcrição segundo análise categorial temática de conteúdo. Os resultados evidenciaram qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
0
0
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
1
0
0
5
Order By: Relevance
“…In the category health, the mothers' knowledge about the protective effect of breast milk and the nutritional value of this food was evident. These findings are in agreement with what was found by Eulálio et al 21 , who observed the perception that breast milk promotes healthy growth and development of the infants, in the interviewees' speech. This result evidences the incorporation, by the mothers, of the technical-scientific discourse used both in the BF campaigns and in the assistance given by health professionals to the nursing mothers.…”
Section: Discussionsupporting
confidence: 93%
“…In the category health, the mothers' knowledge about the protective effect of breast milk and the nutritional value of this food was evident. These findings are in agreement with what was found by Eulálio et al 21 , who observed the perception that breast milk promotes healthy growth and development of the infants, in the interviewees' speech. This result evidences the incorporation, by the mothers, of the technical-scientific discourse used both in the BF campaigns and in the assistance given by health professionals to the nursing mothers.…”
Section: Discussionsupporting
confidence: 93%
“…Esse estudo, demonstra a necessidade dos profissionais em compreender os anseios das mães para apoiar de forma efetiva a vivência da amamentação. O medo do parto pode ser minimizado com o suporte do profissional de enfermagem qualificado nas práticas humanizadoras no ambiente de parto, corroborando para a redução da morbimortalidade materna e neonatal, (Eulálio, 2014); (Ferreira, 2013).…”
Section: Resultsunclassified
“…Para os defensores dessa teoria como Bentham e Singer, a moralidade é calculada levando-se em conta as consequências do ato sobre todos os seres dotados de sensibilidade e as ações corretas são as que produzem o maior equilíbrio possível entre felicidade e infelicidade 18 .…”
Section: B9unclassified
“…A felicidade a que se referem está ligada aos prazeres inferiores como as necessidades físicas de ordem sensorial e aos prazeres superiores, que são de ordem intelectual, estética e social 18 .…”
Section: B9unclassified
See 1 more Smart Citation